Faktor–Faktor yang Mempengaruhi Keselamatan Tenaga Kerja Bongkar Muat di PT. Pelindo Multi Terminal Branch Belawan (International Forum of Researchers and Lecturers, 2023)
PT Pelindo Multi Terminal is a subsidiary of the state-owned PT Pelabuhan Indonesia (Persero) which manages port business entities in the field of multipurpose terminal operations in Indonesia, such as liquid bulk, dry bulk, general cargo, and so on. PT Pelindo Multi Terminal / SPMT as the leading provider of non-container terminal services in Indonesia provides various services to service users. The services provided by SPMT include Stevedoring, Haulage, Receiving/Delivery, Stacking, Dock Services and Other Services. PT Pelindo Multi Terminal has a high commitment to implementing the principles of Good Corporate Governance (GCG) consistently and continuously. PT Pelindo Multi Terminal is responsible for loading and unloading activities at the port. Stevedoring Workers (TKBM) have an important role in achieving the performance of loading and unloading activities from the port to the ship and from the ship to the port. Loading and unloading workers are one part of the workforce that needs attention because the work process they carry out carries the risk of work accidents. Work safety issues are factors that must be taken into account when carrying out loading and unloading work at the port. To obtain data the author used the Field Research method together with employees of PT Pelindo Multi Terminal Belawan using interviews. The library research method is also used by reading books and research results related to the paper writer's object obtained from libraries and other trusted sources.